Enhancing Customer Satisfaction at PT Bank Rakyat Indonesia (Persero) Tbk: The Impact of Service Quality - Pratiwi, Wanda Diah; Budiandru, Budiandru (Jurnal Ecogen, 2024)
The focus of this research aimed to ascertain how customer satisfaction at the Kramat Jati Branch of PT Bank Rakyat Indonesia (Persero) is affected by service quality. This study involved 100 respondents who were bank customers, with the sample size calculated using the Slovin formula and selected through accidental sampling techniques.  At the Kramat Jati Branch of PT Bank Rakyat Indonesia (Persero) Tbk, customers were asked to fill out questionnaires to provide primary data. The analysis showed that the estimated t-value (6.393) was higher than the t-table value (1.984), and the significance coefficient was 0.000, which is less than the standard threshold of 0.05. These results indicate that service quality significantly influences customer satisfaction. Analysis with SPSS shows that service quality contributes 29.4% to customer satisfaction, and the correlation test shows that the relationship between service quality and customer satisfaction is in the medium category with a coefficient value of 0.542.